Integrated Geospatial and Statistical Approaches for Debris Flow Susceptibility in Panataran River, Sabah, Malaysia: A Case Study Post-2015 Earthquake - Kamilia Sharir; Woon Zhan Wen; Arina Ismail; Rodeano Roslee (Geography, Earth Science and Environment: Research Highlights Vol. 1, 2024)
This chapter presents an expanded analysis of debris flow susceptibility in the Panataran River, Kg Melangkap, Sabah, Malaysia, following the 2015 earthquake. The study area, located on the North-West flank of Mount Kinabalu, is characterized by complex geomorphology, influenced by both tectonic and climatic factors. Using an integrated approach combining geospatial techniques with bivariate statistical analysis, specifically the Frequency Ratio (FR) model, the study identifies key factors contributing to debris flow susceptibility. The expanded chapter includes updated datasets and new geospatial visualizations, enhancing the predictive accuracy of the susceptibility model. Validation using the Area Under Curve (AUC) method demonstrates a high accuracy of 81.8%, confirming the model’s effectiveness for regional hazard management and land-use planning.